Craft products from poultry meat - Pasichnyi, Vasyl; Chernyushok, Olga; Poloz, Denys; Harmash, Anna; Yakuts, M. (My University, 2024)
Craft poultry products have become a prominent segment in the broader craft food industry, offering consumers high-quality, artisanal alternatives to mass-produced items. These products are typically made using traditional techniques and natural ingredients, which appeal to consumers seeking more authentic, flavorful, and health-conscious options.
Keywords: кафедра технології м’яса і м’ясних продуктів; craft products; poultry mea; traditional technologie; крафтові вироби; м'ясо птиці; традиційні технології